Redefining rape : sexual violence in the era of suffrage and segregation - Freedman, Estelle B., 1947- (Harvard University Press, 2013)
Rape has never had a universally accepted definition, and the uproar over "legitimate rape" during the 2012 U.S. elections confirms that it remains a word in flux. This book tells the story of the forces that have shaped the meaning of sexual violence in the United States, through the experiences of accusers, assailants, and advocates for change. In this new history, the author demonstrates that our definition of rape has depended heavily on dynamics of political power and social privilege. The long-dominant view of rape in America envisioned a brutal attack on a chaste white woman by a male stranger, usually an African American. From the early nineteenth century, advocates for women's rights and racial justice challenged this narrow definition and the sexual and political power of white men that it sustained. Between the 1870s and the 1930s, at the height of racial segregation and lynching, and amid the campaign for woman suffrage, women's rights supporters and African American activists tried to expand understandings of rape in order to gain legal protection from coercive sexual relations, assaults by white men on black women, street harassment, and the sexual abuse of children. By redefining rape, they sought to redraw the very boundaries of citizenship. Here the author narrates the victories, defeats, and limitations of these and other reform efforts. The modern civil rights and feminist movements, she points out, continue to grapple with both the insights and the dilemmas of these first campaigns to redefine rape in American law and culture.-- Publisher information